2007
DOI: 10.1007/s00228-007-0268-6
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin anticoagulants and co-trimoxazole: avoid the combination rather than manage the interaction

Abstract: Objective The objective of our study was to examine the management of the interaction between acenocoumarol or phenprocoumon and several antibiotics by anticoagulation clinics and to compare the consequences of this interaction on users of co-trimoxazole with those for users of other antibiotics. Methods A follow-up study was conducted at four anticoagulation clinics in The Netherlands. Data on measurements of the International Normalised Ratio (INR), application of a preventive dose reduction (PDR) of the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Trimethoprim is a relatively selective inhibitor of CYP2C8 [15]. Hauta-Aho et al [16] reported that the risk of bleeding related to VKA drug interactions in hospitalized patients was greatest with CYP 2C9 inhibitors, of which TMP-SMX would appear to be the most potent of interacting antibiotics [17][18][19]. At typically achieved SMX serum concentrations, there is a 20%-30% inhibition of CYPC29, consistent with observed VKA dose reduction requirements when used together.…”
Section: Pharmacology Of the Vka-tmp-smx Interactionsupporting
confidence: 60%
See 1 more Smart Citation
“…Trimethoprim is a relatively selective inhibitor of CYP2C8 [15]. Hauta-Aho et al [16] reported that the risk of bleeding related to VKA drug interactions in hospitalized patients was greatest with CYP 2C9 inhibitors, of which TMP-SMX would appear to be the most potent of interacting antibiotics [17][18][19]. At typically achieved SMX serum concentrations, there is a 20%-30% inhibition of CYPC29, consistent with observed VKA dose reduction requirements when used together.…”
Section: Pharmacology Of the Vka-tmp-smx Interactionsupporting
confidence: 60%
“…In such patients the VKA should be started at lower doses (20%-40% of usual), INR monitored carefully (sooner and more often), and doses titrated slower (due to the interaction-related longer half-life of the S-enantiomer of VKA). Similarly, careful INR monitoring with VKA dose adjustment is needed to avoid undercoagulation if chronic TMP-SMX is discontinued [19,57].…”
Section: Is Routine Inr Monitoring Adequate When Managing Patients Comentioning
confidence: 99%
“…However, in a review of a healthcare claims database in Canada, rivaroxaban was associated with a significantly lower risk of nonadherence compared with warfarin (hazard ratio for cessation = 0.66) [ 34 ]. This could be different from the situation in Netherlands because of the therapeutic VKA monitoring by specialised anticoagulation clinics [ 35 ]. To ensure an optimal antithrombotic effect, continuous and regular intake of NOACs is necessary [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 89%
“…It has been known that environmental and clinical factors, such as age, height, body weight, co-medications and dietary vitamin K intake, influence warfarin dose requirements. [1][2][3][4] In addition, the contribution of genetic factors to interindividual variability has become increasingly appreciated in recent years. Over 40% of the variance in warfarin dose could be attributed to genetic variants in both cytochrome P450 (CYP) 2C9 and vitamin K epoxide reductase complex subunit 1 (VKORC1) genes.…”
Section: Introductionmentioning
confidence: 99%